GAYA HIDUP SEKSUAL WARIA NON PEKERJA SEKS KOMERSIAL KOTA SEMARANG - Dewi Rokhmah; Yennike Tri Herawati (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Being transvestites is not merely bringing a biological problems, but also psychological and sociological. Most transvestites were having a low self concept due to their confusion on their sexual identity. The ambiguity place them isolated from community. Social pressure forms stigmatization and discrimination toward thisgroup of people, which lead them to have more risky sexual practice. This study aims to analize the sexual life style of non-commercial transvestites in Semarang.